Compartmentalized Human Immunodeficiency Virus Type 1 Reservoir in Intestinal Monocytes/Macrophages on Antiretroviral Therapy - Vellas, Camille; Martres, Dorine; Requena, Mary; Nayrac, Manon; Collercandy, Nived; Latour, Justine; Barange, Karl; Alric, Laurent; Martin-Blondel, Guillaume; Izopet, Jacques; Lagane, Bernard; Delobel, Pierre (The Journal of infectious diseases, 2025)
The intestinal mucosa contains many cells targeted by human immunodeficiency virus type 1 (HIV-1), and high levels of HIV-1 DNA persist in this compartment under antiretroviral therapy (ART). While CD4+ T cells are the best-characterized reservoir of HIV-1, the role of long-lived intestinal macrophages in HIV-1 persistence on ART remains controversial. We collected duodenal and colonic biopsies from 12 people with HIV (PWH) on suppressive ART, enrolled in the ARNS EP61 GALT study. Total, integrated, intact and defective HIV-1 proviruses were quantified from sorted T cells and monocytes/macrophages. HIV-1 env quasispecies were analyzed by single-molecule next-generation sequencing and env-pseudotyped viruses were constructed to assess macrophage versus T-tropism. Total HIV-1 DNA levels in intestinal T cells were significantly higher than those in monocytes/macrophages (P < .0001). Unintegrated HIV-1 DNA was detected in one-third of T-cell and monocyte/macrophage-positive samples. Intact HIV-1 proviruses were detected using the intact proviral DNA assay in 4 of 16 T-cell samples and 1 of 6 monocyte/macrophage samples with detectable HIV-1 DNA. HIV-1 sequences were compartmentalized between intestinal monocytes/macrophages and T cells in some subjects. Phenotypic analysis of pseudotyped viruses expressing HIV-1 envelopes from colonic monocytes/macrophages revealed T-tropism rather than M-tropism. Our results show that monocytes/macrophages from the intestinal mucosa of PWH on ART can contain HIV-1 DNA, including intact or unintegrated forms, but at much lower levels than those found in T cells, and with some compartmentalization, although they do not exhibit a specific macrophage tropism, raising the question of the mechanisms of infection involved.